2020
DOI: 10.1177/2056305120963760
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Fear of Missing Out, Problematic Smartphone Use, and Social Networking Services Fatigue Among Young Adults

Abstract: In this study, we aimed to adapt the Information and communication technology (ICT) Overload and social networking service (SNS) Fatigue Scale to measure the overload and SNSs fatigue experienced by individuals while using ICTs in the Turkish language and analyze the adapted scale based on various variables. The scale adaptation procedure was conducted by surveying 225 undergraduate-level university students. In addition to discriminant and convergent reliability, the general fitness index parameters were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 74 publications
3
23
0
2
Order By: Relevance
“…There is no consensus on a concept that captures the meaning of declining interest within the number of active users. 4 Although many authors define this phenomenon differently, using terms such as "social network fatigue," 10,13,14 "social networking services fatigue," 12,15 "social media burnout," 4,16 and "social media fatigue," 3,5,11,[17][18][19] all of them adhere to the same type of trend related to quitting or abandoning social networking services. Given that social media fatigue (hereinafter: SMF) seems to be the most popular and common term in the scientific publications, we decided to assume this concept in the present research.…”
Section: Literature Review Social Media Fatiguementioning
confidence: 99%
See 2 more Smart Citations
“…There is no consensus on a concept that captures the meaning of declining interest within the number of active users. 4 Although many authors define this phenomenon differently, using terms such as "social network fatigue," 10,13,14 "social networking services fatigue," 12,15 "social media burnout," 4,16 and "social media fatigue," 3,5,11,[17][18][19] all of them adhere to the same type of trend related to quitting or abandoning social networking services. Given that social media fatigue (hereinafter: SMF) seems to be the most popular and common term in the scientific publications, we decided to assume this concept in the present research.…”
Section: Literature Review Social Media Fatiguementioning
confidence: 99%
“…Bright and colleagues 17,23 defined SMF as a user's tendency to retreat from social network engagement when they are overloaded with too much information. Other studies showed that SMF refers to suffering from mental 12,18 or emotional 16,24 exhaustion, and manifests itself in decreased interest in accessing to social platforms. 4,10 The presented definitions confirm that SMF reflects a multidimensional user experience 5 in cognitive, behavioral, and emotional dimensions.…”
Section: Literature Review Social Media Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…Also, it is referred to as “a subjective, multidimensional user experience comprising feelings such as tiredness, annoyance, anger, disappointment, guardedness, loss of interest, or reduced need/motivation associated with various aspects of SNS use and interactions” (Ravindran et al , 2014). In addition, SNS fatigue has also been determined as an adverse emotional reaction or mental condition relating to individuals' SNS usages and activities (Hwang et al , 2019; Tugtekin et al , 2020; Zhang et al , 2016).…”
Section: Theoretical Backgroundsmentioning
confidence: 99%
“…However, some negative effects can result from obsessive social media use, including psychological and physical stress and strain (Zhu & Bao, 2018), as users are constantly encouraged to stay in touch, maintain interest, and respond to a huge amount of information on social networking platforms (Lee et al, 2016). The negative impact of social network usage has been referred to as "social networking service fatigue" in the literature (Lee et al, 2016;Tugtekin et al, 2020;Zhang et al, 2016). The current study examines the information and communication technology overload and social networking fatigue levels of young college students using the "Information and Communication Technology Overload & Social Networking Service Fatigue Scale" developed by Lee et al (2016), which was adapted into Turkish by Tugtekin et al (2020).…”
Section: Extended Abstract Introductionmentioning
confidence: 99%